Modelling Android applications through static analysis and systematic exploratory testing - Ventresque, Anthony; Laurent, Thomas; Doyle, Jordan (IEEE, 2023)
Mobile application development is a fast paced industry with frequent releases. While the development pace increases, so too does the need for automated test generation. Model-based test generation is one of the most common and successful approaches to support this need. Understanding and modelling the application under test is integral to producing comprehensive, dependable and effective tests. Unfortunately, mobile platforms such as Android, introduce a host of diffi- culties. Static analysis struggles with Android’s event-based nature and the growing variety of mechanisms available for developers to implement different features. Additionally, dy- namic analysis, implemented by popular random test genera- tors, is slow, inefficient, and limited by a lack of application knowledge. This paper introduces DroidGraph, a framework to generate a comprehensive control flow model of Android applications using traditional static analysis and efficient systematic ex- ploratory tests. DroidGraph provides a detailed model of an Android application, from low level method statements to high level user interface structures. This model can be used to support automated test generation. We apply DroidGraph to 19 diverse apps and show that our efficient exploratory tests, on average, interact with 18% more of the app than commonly used random exploration in 345 less interactions. Integrating the dynamic analysis results provided by these tests complements our static analysis, and uncovers on average 51 more components and 49% more interface callback links in the application code.
International Conference on Dependable Systems and Their Applications (DSA)
Keywords: Automated testing; Android, Static analysis, Exploratory testing